2012
DOI: 10.7883/yoken.65.301
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Intussusception as Studied from a Hospital-Based Retrospective Survey over a 10-Year Period (2001^|^ndash;2010) in Akita Prefecture, Japan

Abstract: SUMMARY:One concern about rotavirus vaccines is its possible association with intussusception. Thus, it is necessary to determine the baseline incidence for intussusception in the first year of life in places where rotavirus vaccines are introduced. However, few safety data exist for the period at which the first dose of Rotarix and RotaTeq are allowed to administer in Japan. The first dose of Rotarix is scheduled to administer at 6-20 weeks of age and that of RotaTeq is scheduled to administer at 6-24 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
1
20
1
Order By: Relevance
“…A hospital-based study carried out between 1995 and 1999 in Hanoi, Hue, Ho Chi Minh city suggested a frequent occurrence of intussusception in children less than 12 months of age in Vietnam, with cases occurring in the range of 472 to 722 each year [13]. The incidence in Vietnam was considerably higher than in any neighboring country, including Japan with 185 per 100,000 person-years (95% CI: 133–251) [14] or 158 per 100,000 person-years (95% CI: 131–188) [15], Hong Kong with 108 per 100,000 person-years (95% CI: 95.3–119.7) [16], Taiwan with 77 per 100,000 person-years (range 64.2–86.5) [17], Singapore with 22.8–100.8 per 100,000 [18], Thailand with 19.7–47.8 per 100,000 person-years [11] and Malaysia with 17.8 per 100,000 person-years [19]. …”
Section: Discussionmentioning
confidence: 99%
“…A hospital-based study carried out between 1995 and 1999 in Hanoi, Hue, Ho Chi Minh city suggested a frequent occurrence of intussusception in children less than 12 months of age in Vietnam, with cases occurring in the range of 472 to 722 each year [13]. The incidence in Vietnam was considerably higher than in any neighboring country, including Japan with 185 per 100,000 person-years (95% CI: 133–251) [14] or 158 per 100,000 person-years (95% CI: 131–188) [15], Hong Kong with 108 per 100,000 person-years (95% CI: 95.3–119.7) [16], Taiwan with 77 per 100,000 person-years (range 64.2–86.5) [17], Singapore with 22.8–100.8 per 100,000 [18], Thailand with 19.7–47.8 per 100,000 person-years [11] and Malaysia with 17.8 per 100,000 person-years [19]. …”
Section: Discussionmentioning
confidence: 99%
“…The incidence has declined in the UK, from 0.86 (1997–1998) to 0.34 (2008–2009) per 1000 live births ; in Australia, New Zealand and the USA, 0.5–2.3 cases per 1000 live births have been reported; and in Japan, 1.8–1.9 per 1000 infants have been reported . Japanese data for 2001–2010 showed an intussusception incidence of 185 per 100 000 person years under the age of one year, with 10 per 100 000 at the age of zero to two months, 165 per 100 000 at the age of three to five months and three per 100 000 at the age of six to eight months .…”
Section: Methodsmentioning
confidence: 99%
“…The number of cases expected to occur within 7 and 30 days following vaccination ( Ne ) was derived from the following formula: Ne=truetrue∑i=112Inc×Pdi×Ndi30.4×RP, where Inc = the incidence of IS cases in the first year of life. The incidence value used for Japan was based on the paper of Noguchi et al (158/100 000 person‐years) Pd i = the proportion of IS cases occurring in the i th month of age.…”
Section: Methodsmentioning
confidence: 99%
“… Pd i = the proportion of IS cases occurring in the i th month of age. Japanese age‐specific distributions were used Nd i = the number of doses of Rotarix TM distributed in the i th month of age, based on country‐level sales data and an estimate of the age of vaccine administration based on the distribution of age at vaccination spontaneously reported in Rotarix TM cases available in the GSK spontaneous report database. RP = the risk period in days (e.g., 7 or 30 days). 30.4 = the average number of days in a month. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation